Islamic Hospitality and the Fight Against Islamophobia: The Essential Role of Sharia-Compliant Hotels - Rakhman Priyatmoko (UIN Raden Mas Said Surakarta, 2024)
The escalating Israel-Palestine conflict triggered a surge in Islamophobia and hate crimes against Muslims worldwide. As part of the Islamic hospitality industry, Sharia-compliant hotels played a crucial role in promoting the values of Islamic hospitality to non-Muslim tourists, with the aim of reducing Islamophobia. Utilizing a literature review approach, this research aims to answer two main questions, 1) how Islamophobia affects the Muslim community in general, and 2) how Islamic hospitality values in Sharia-compliant hotels play an important role in reducing Islamophobia. The study identified that Sharia-compliant hotels had at least four promotable products and services, namely halal food products, the prohibition of alcoholic beverages, protection for female and child tourists, and religion-based preference room services. Practically, this research provides references to Sharia-compliant hotel managers regarding Islamic hospitality values that can be promoted to attract non-Muslim tourists. Effective promotion of the values of Islamic hospitality could significantly contribute to mitigating Islamophobia and its negative impacts, including the rise in hate crimes. In the future, scholars and Islamic researchers needed to engage in more comprehensive research to formulate strategies that captured the hearts of non-Muslim tourists and countered Islamophobia.